A pangalactic gargle blaster of Lilliputian proportions: A comparative analysis of Jonathan Swift's Gulliver's Travels and Douglas Adams's The Hitchhiker's Guide to the Galaxy - Brown, Molly (University of Pretoria, 2017)
Dissertation (MA)--University of Pretoria, 2017.